PERAN FAKTOR-FAKTOR SOSIAL EKONOMI DALAM USAHATANI LADANG BERPINDAH DI KAMPUNG TERING LAMA ULU KECAMATAN TERING KABUPATEN KUTAI BARAT (The Role of Socioeconomic Factors in Shifting Cultivation in Tering Lama Ulu Village, Tering Subdistrict, West Kutai District) - DARMANUS LUNG; RITA MARIATI; TETTY WIJAYANTI (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2018)
The purpose of this research was to know how big the role of factors such as age, education level, household income, land area, and number of family dependent for farmers in choosing to do shifting cultivation. This research was conducted in Tering Lama Ulu Village, Tering Subdistrict, West Kutai District. This research was conducted from June to July 2017. The sampling method used census method. Data collection was conducted through interviews to 20 respondents and observations at the study sites. Factors that play a role for farmers in shifting cultivation were analyzed by using Likert scale measurement method by using 5 indicators. The results of this study indicate the average number obtained was 6.75 which meant the role of factors such as age, education level, number of family dependents, land area, and household income on farmers' decisions on shifting cultivation starting from the process of exemption, felling of trees, burning, preparation for planting, weeding, harvesting, and post-harvesting. The conclusion of this research showed that age, education level, number of family dependents, land area, and household income, play role for farmers on shifting cultivation in Tering Lama Ulu.